Blind signatures from Zero knowledge in the Kummer variety - Barreto, Paulo L.; Reich, Devin D.; Simplicio Jr., Marcos A.; Zanon, Gustavo H. M. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2023)
We show how to apply the BZ methodology (Blind signatures from Zero knowledge) to obtain blind signatures in the Kummer varieties defined by Montgomery curves. We also describe specially-tailored arithmetic algorithms to facilitate its efficient implementation. The result can be proved secure under appropriate assumptions, appears to resist even the ROS attack (to which most elliptic-curve blind signature schemes succumb), and is arguably one of the most efficient among those proposals that offer similar security guarantees.